Pengaruh modal sosial terhadap kebahagiaan generasi sandwich di Indonesia - Amelia Rahman; Turro Seltris Wongkaren (Research Centre for Population, National Research and Innovation Agency (BRIN), 2022)
The measure of welfare is not only about material prosperity but also about happiness. The sandwich generation has a dual role to play in influencing their happiness. On the other hand, social capital also affects happiness. There are several mechanisms by which social capital affects happiness, including health conditions, household income, and education. This study aims to analyze specifically how social capital influences the happiness of the sandwich generation in Indonesia. This study uses SPTK 2017 data, analyzing the head of household or partner of the sandwich generation and non-sandwich generation. Using OLS estimation, the study found that the happiness index in the sandwich and non-sandwich generations are not significantly different. However, social capital generally has a significant effect on happiness. In addition, health conditions were found to be a variable that becomes a mechanism for how social capital affects happiness. Increasing the value of social capital in the poor health sandwich generation will be more beneficial in increasing their happiness. Meanwhile, household income and education were not found to be mechanisms for social capital.